Trypanosoma congolense: Comparative effects of a primary infection on bone marrow progenitor cells from N'Dama and Boran cattle - Andrianarivo, A.G.; Muiya, P.; Opollo, M.; Logan-Henfrey, L.L. (Elsevier, 1995)
Using in vitro clonogenic assays, the changes in haemopoietic progenitor cell levels were compared in the bone marrow of three adult trypanotolerant N'Dama cattle and three age-matched trypanosusceptible Boran cattle over 17 weeks (119 days) of a primary Trypanosoma congolense (clone IL 1180) infection. As the infection progressed, a clear tendency of the parasitaemia to decrease was seen in the N'Damas, while it remained high throughout the infection in the Borans. The decline in the colony-forming units-granulocyte macrophage (CFU-GM) between 7 and 42 days positinfection (dpi) corresponded withthe decreased numbers of neutrophils and monocytes in the blood observed in both breeds. Thereafter, a further significant drop in the CFU-GM levels was observed in the Borans which may partially explain the continued decrease in the numbers of neutrophils and monocytes in blood. In contrast, a significant peak of CFU-GM above preinfection levels was observed in the N'Damas on 49 dpi, which could partially explain the subsequent recovery of the numbers of neutrophils and monocytes in blood. When compared to the N'Damas, the Borans had a more dramatic drop in the packed cell volume (PCV) from 25 dpi onwards, resulting in significantly lower PCFrom 46-49 dpi on wards, the mean PCV stabilised at significantly lower levels in the Borans than in the N'Damas. The mean corpuscular volume (MCV) levels increased in both breeds, but at a much faster rate in the Borans. The clonogenic assays demonstrated an erythropoietic response, characterised by peaks above preinfecton levels of both the early and late erythroid progenitor cells (respectively, burstforming units-erythroid, BFU-E, and colony-forming units-erythroid, CFU-E), occurring between 35 and 70 dpi in both breeds of cattle. However, despite a more severe anaemia in the Borans, the magnitude of their erythroid response was similar to that of the N'Damas, suggesting that the response of the Borans was insufficient to compensate for the greater degree of anaemia. Moreover, the mean PCV did not improve in the Borans, indicating the ineffectiveness of their erythropoietic response. An increased rate of erythrocyte destruction and/or a defective differentiation and maturation of erythroid precursors have also been shown to be partially responsible for this persistent anaemia. From 98 dpi onwards, despite the persistent low PCV, the MCV decreased to preinfection levels and low CFU-E numbers were observed in the Borans. Over the same period, in the N'Damas the N'Damas the mean PCV progressively increased to reach 25 percent, which fell within the low normal range for cattle. This may partially explain the return of the BFU-E to preinfection levels and the slight decrease in the CFU-E in the N'Damas. During the acute phase of a T. congolense infection, both the granulomonocytic and erythroid progenitors were increased more effectively in the N'Dama cattle than in the Boran cattle, when compared to the degree of cytopaenia in blood; this might correlate with the superior ability of the N'Damas to maintain gigher numbers of granulocytes, monocytes, and erythrocytes in blood.